Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

Neurogenomic landscape associated with status‐dependent cooperative behaviour - Peri E. Bolton; T. Brandt Ryder; Roslyn Dakin; Jennifer L. Houtz; Ignacio T. Moore; Christopher N. Balakrishnan; Brent M. Horton (Molecular Ecology, 2025)
The neurogenomic mechanisms mediating male–male reproductive cooperative behaviours remain unknown. We leveraged extensive transcriptomic and behavioural data on a neotropical bird species ( Pipra filicauda ) that performs cooperative courtship displays to understand these mechanisms. In this species, the cooperative display is modulated by testosterone, which promotes cooperation in non‐territorial birds, but suppresses cooperation in territory holders. We sought to understand the neurogenomic underpinnings of three related traits: social status, cooperative display behaviour and testosterone phenotype. To do this, we profiled gene expression in 10 brain nuclei spanning the social decision‐making network (SDMN), and two key endocrine tissues that regulate social behaviour. We associated gene expression with each bird's behavioural and endocrine profile derived from 3 years of repeated measures taken from free‐living birds in the Ecuadorian Amazon. We found distinct landscapes of constitutive gene expression were associated with social status, testosterone phenotype and cooperation, reflecting the modular organization and engagement of neuroendocrine tissues. Sex‐steroid and neuropeptide signalling appeared to be important in mediating status‐specific relationships between testosterone and cooperation, suggesting shared regulatory mechanisms with male aggressive and sexual behaviours. We also identified differentially regulated genes involved in cellular activity and synaptic potentiation, suggesting multiple mechanisms underpin these genomic states. Finally, we identified SDMN‐wide gene expression differences between territorial and floater males that could form the basis of ‘status‐specific’ neurophysiological phenotypes, potentially mediated by testosterone and growth hormone. Overall, our findings provide new, systems‐level insights into the mechanisms of cooperative behaviour and suggest that differences in neurogenomic state are the basis for individual differences in social behaviour.

Population structure and reproductive states of the dogwhelk Nucella lapillus differ between artificial structures and natural rocky shores - Bryan Thompson; Paul R. Brooks; Veronica Farrugia Drakard; Fiona Kubin; Hannah S. Earp; Ignacio Alvarez-Cienfuegos; Pippa J. Moore; Tasman P. Crowe (Marine Environmental Research, 2023)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Ovine Abortion by Neospora caninum: First Case Reported in Argentina - Yanina P. Hecker; Eleonora L. Morrell; María A. Fiorentino; Ignacio Gual; Emilia Rivera; Franco Fiorani; Matías A. Dorsch; María L. Gos; Lais L. Pardini; María V. Scioli; Sergio Magariños; Fernando A. Paolicchi; et al. (Acta Parasitologica, 2019)

Male parental investment reflects the level of partner contributions and brood value in tree swallows - Ádám Z. Lendvai; Çağlar Akçay; Mark Stanback; Mark F. Haussmann; Ignacio T. Moore; Frances Bonier (Behavioral Ecology and Sociobiology, 2018)

Evaluation of frequency of antibodies against Toxoplasma gondii,Neospora caninum and Sarcocystis spp. and transmission routes in sheep from Humid Pampa, Argentina - Yanina P. Hecker; Fernando Mogaburu Masson; Joaquín I. Armendano; Juan Cora; Carlos Flores Olivares; Ignacio Gual; Lais Pardini; Dadín P. Moore; Gastón Moré; Germán J. Cantón (Acta Parasitologica, 2018)
The aim of this study was to describe the frequency of ovine specific antibodies to Toxoplasma gondii , Neospora caninum and Sarcocystis spp. and to estimate different transmission routes of these infections. One hundred and thirty Texel sheep and their 117 Texel lambs were included in the study. Serum samples were tested for antibodies to T . gondii , N . caninum and Sarcocystis spp. using IFAT. Toxoplasma gondii seroprevalence was 10.00% in sheep (IC 95% : 4.80–15.20%), being higher in adult sheep (≥12 year) than in younger sheep (OR 1.30; 95% CI, 1.10–1.50). N . caninum and Sarcocystis spp. seroprevalences were 1.54% (IC 95% : 0.00–5.70) and 72.09% (IC 95% : 67.70–82.70), respectively, with no association between age and seropositivity in sheep ( P >0.05). T . gondii seroprevalence in lambs was 4.27% (IC 95% : 0.61–7.94). No association between T . gondii serological status in sheep and their lambs was detected ( P = 0.07). Two T . gondii and Sarcocystis spp. seropositive lambs were euthanized and T . gondii and Sarcocystis spp. DNA was detected by PCR in their tissues. In conclusion, the increase of T . gondii seropositivity in relationship with sheep age and the lack of association between sheep-lamb serological status, suggest that horizontal infection is the main transmission route in this flock as reported before. Due to the low number of N . caninum -seropositive ewes no assumptions can be done about the impact of this parasite in this flock. According with previous reports, the main transmission route for Sarcocystis spp. in this species in the present study was horizontal.

An Ibero-American inter-laboratory trial to evaluate serological tests for the detection of anti-Neospora caninum antibodies in cattle - Lucía M. Campero; Javier Moreno-Gonzalo; María C. Venturini; Gastón Moré; Andrea Dellarupe; Magdalena Rambeaud; Ignacio E. Echaide; Beatriz Valentini; Carlos M. Campero; Dadín P. Moore; Dora B. Cano; Marcelo Fort; et al. (Tropical Animal Health and Production, 2018)

Parasites, mate attractiveness and female feather corticosterone levels in a socially monogamous bird - François Mougeot; Ádám Z. Lendvai; Jesús Martínez-Padilla; Lorenzo Pérez-Rodríguez; Mathieu Giraudeau; Fabián Casas; Ignacio T. Moore; Steve Redpath (Behavioral Ecology and Sociobiology, 2016)

Effects of food supplementation on a tropical bird - Alexandra M. Class; Ignacio T. Moore (Oecologia, 2013)

Green abalone, Haliotis fulgens infected with the agent of withering syndrome do not express disease signs under a temperature regime permissive for red abalone, Haliotis rufescens - James D. Moore; Christy I. Juhasz; Thea T. Robbins; L. Ignacio Vilchis (Marine Biology, 2009)

Endocrine responsiveness to social challenges in northern and southern hemisphere populations of Zonotrichia - John C. Wingfield; Simone L. Meddle; Ignacio Moore; Shallin Busch; Douglas Wacker; Sharon Lynn; Aaron Clark; Rodrigo A. Vasquez; Elizabeth Addis (Journal of Ornithology, 2007)

Population frequencies of alternative male phenotypes in tree lizards: geographic variation and common-garden rearing studies - Diana K. Hews; Christopher W. Thompson; Ignacio T. Moore; Michael C. Moore (Behavioral Ecology and Sociobiology, 1997)